2021
DOI: 10.1016/j.ejogrb.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal sampling for PCR-testing in the investigation of SARS-COV-2 vertical transmission in pregnancy

Abstract: The novel COVID-19 global pandemic has raised, among many others, major concerns regarding the impact of infection during pregnancy. Current evidence suggests that vertical transmission from mother to baby, antenatally or intrapartum, does occur, but is uncommon. According to the published reports of infants born to COVID-19-affected mothers, as well as the anecdotal experience of current practices worldwide, it appears that investigations regarding the potential of SARS-COV-2 vertical transmission in pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Several studies conducted in Asian countries have indicated high (83.6%) knowledge levels of COVID-19 among the general population which is similar to our findings (33). The findings of our study tells us the importance of educating non-teaching faculties about Coronavirus transmission and also the preventive measures that play a vital role in their protection from getting infected with the disease and which dramatically reduce the spread of the disease,while comparing with the previous study, people who knew about the route of transmission was 78.3% where people are more aware of COVID-19 transmission in this study than previous study (34). This study has several limitations.…”
Section: Resultssupporting
confidence: 87%
“…Several studies conducted in Asian countries have indicated high (83.6%) knowledge levels of COVID-19 among the general population which is similar to our findings (33). The findings of our study tells us the importance of educating non-teaching faculties about Coronavirus transmission and also the preventive measures that play a vital role in their protection from getting infected with the disease and which dramatically reduce the spread of the disease,while comparing with the previous study, people who knew about the route of transmission was 78.3% where people are more aware of COVID-19 transmission in this study than previous study (34). This study has several limitations.…”
Section: Resultssupporting
confidence: 87%
“…Although uncommon, vertical transmission of SARS-CoV-2 virus has been demonstrated with the reverse transcriptase–polymerase chain reaction (RT-PCR) technique, and the virus has been detected in the placenta, amnion, and blood of newborns born to mothers infected with the SARS-CoV-2 virus. This vertical transmission was also confirmed with newborns who were positive for the IgM antibodies, which do not cross the placenta ( Badr et al 2020 ; Konstantinidou et al 2021 ).…”
Section: Introductionmentioning
confidence: 63%
“…At present, the extent to which the vertical transmission of SARS-CoV-2 occurs and the timing of such transmission are unclear. Although SARS-CoV-2 intrapartum transmission is possible [2], low incidence rates of in utero transmission [3][4][5][6] and early and late adverse obstetric outcomes [7,8] suggest that the placenta may play a critical role in modulating maternal response to SARS-CoV-2 infection. The main variable is placental permissibility to SARS-CoV-2 entry mechanisms initiated by spike protein (S) attachment to the angiotensin-converting enzyme 2 (ACE2) receptor [9][10][11].…”
Section: Introductionmentioning
confidence: 99%